Ecologia reprodutiva de Phalloceros caudimaculatus, Hensel,1868 (Cyprinodontiformes:poeciliidae) em duas áreas no município de Uberlândia, MG - Vieira, Christian de Mello (2004)
The Poeciliids are Cyprinodontiform fishes, with reduced size, and most of them are viviparous species. They are found on tropical and subtropical latitudes of New World, concentrated on Central America and South America, occurying in fresh water and salty water places. They are called colonizer species, because when only a female stay at a sterile place it can originate a new population. They can support poor places in other species, due to adversities conditions of water. They tolerate salinity and changes at water temperature. They live in marginal microhabitats because of inaccessibility of these areas for this kind of predators. Phalloceros caudimaculatus presents internai fecundation, and the male presents anal fin modified that are called gonopodium. Male and female from two areas of artificial drainage were analised of Clube Caça e Pesca Itororó de Uberlândia at Fazenda Experimental do Glória, from march, 2002 to august, 2003, corresponding to the end of dry season and the end of rainy season, respectively. At females, was analised the fecundity (quantity of embryos per female), the standard length and the reproductive allocation. At males, biometrical measure of standard length and gonopodium length. The results indicated that the species presents a reproductive pick in the beginning of the rainy. The end of the production of embryos for female at rainy season. Seasons it there was signifícant difference among the two areas in that he/she refers to the length of females and males, and in Clube Caça e Pesca they presented. Environment factors as dissolved leveis of oxygen, pH and temperature of the water showed signifícant differences between the areas, what can be associated to the differences in the length and production of embryos and/or eggs.